A philosophically provoking category theory - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Recenzja książki: Elaine Landry (red.), Categories for the Working Philosopher, Oxford University Press, Oxford, 2017, ss. xiv+471.
Keywords: category theory; philosophy